INTEGRATING TRADITIONAL ECOLOGICAL KNOWLEDGE AND ENVIRONMENTAL SCIENCE FOR SUSTAINABLE LAKE CONSERVATION: DANU KERTHI IN BALI - Surpi, Ni Kadek; Seriadi, Si Luh Nyoman; Jemiwi Jero, Ni Wayan (UI Scholars Hub, 2025)
This study investigates how the Danu Kerthi philosophy operates as a framework that integrates Traditional Ecological Knowledge (TEK) with environmental science to support sustainable lake conservation in three upstream lakes in Bali: Beratan, Buyan, and Tamblingan. While previous scholarship has largely focused on the normative and symbolic dimensions of Sad Kerthi, empirical evidence on its ecological effectiveness remains limited. To address this gap, the study adopts a multi-site qualitative design involving participatory observation, document analysis, and semi-structured interviews with 30 participants representing traditional leaders, Hindu priests, tourism managers, village officials, and local residents. Thematic analysis shows that Danu Kerthi continues to function as an ethical and spiritual system that shapes collective awareness of Tirta's sanctity and informs community-based stewardship. However, its practical implementation is constrained by weak enforcement of awig-awig (customary law), tourism pressures, and escalating pollution, particularly plastic waste and agricultural runoff. These constraints are reflected in measurable ecological stress indicators reported in secondary environmental data, including declining water clarity, increased nutrient loading, microplastic contamination, and sedimentation linked to land-use change. The findings reveal a persistent gap between the symbolic potency of ritual practices and their limited capacity to mitigate ecological degradation. This study contributes to eco-theology and TEK discourse by demonstrating that customary environmental ethics remain socially influential but require alignment with formal regulatory instruments and scientific monitoring to achieve tangible ecological improvements. The implications underscore the need for adaptive conservation models that integrate customary values, environmental policy, and empirical ecological data to strengthen the long-term sustainability of Bali’s upland lake ecosystems.